A Green Approach to Preparing Bio-Inhibitor for Mild Steel Corrosion in Different Acid Mediums - Poongothai, N; Athira, R; K. Neena, P (International Journal of Engineering and Technology, 2018)
Inhibition efficiency (I. E) of various concentrations of Carica Papaya (C. P)extracts on the corrosion of mild steel (MS) in 1M HCl and 0.5M H2SO4medium was investigated by weight loss and electrochemical methods at room temperature and elevated temperature. Acid extract of C. P was characterized by using FTIR and XRD spectral studies to identify the major constituents present in it. Zeta potential and EDAX analysis were carried out for the extract to identify electrochemical aspect of a particleâ€™s surface, and information about a particleâ€™s dispersibility, aggregability, and adhesion ability can be obtained from this measurement.Â Surface analysis studies such as FESEM and contact angle measurement were carried out for the C. P extracts to locate the surface coverage of the inhibitor and confirm the hydrophilic nature on the metal surface. Langmuir and Temkin adsorption isotherm confirm the mono layer adsorption and heterogeneity of the MS surface. Thermodynamic dataâ€™s such as activation energy, Gibbs free energy, enthalpy and entropy changes were calculated using weight loss measurements data at room as well as elevated temperatures and identified free energy of adsorption and exothermic reaction taking place during corrosion process. Phytochemical studies confirm the presence of chemical constituents with hetero atom that provide more I.E due to its adsorption of inhibitor on metal surface.Â Â